Aminopurvalanol A, a Potent, Selective, and Cell Permeable Inhibitor of Cyclins/Cdk Complexes, Causes the Reduction of in Vitro Fertilizing Ability of Boar Spermatozoa, by Negatively Affecting the Capacitation-Dependent Actin Polymerization - Bernabò, Nicola; Valbonetti, Luca; Greco, Luana; Capacchietti, Giulia; Ramal Sanchez, Marina; Palestini, Paola; Botto, Laura; Mattioli, Mauro; Barboni, Barbara (Frontiers in Physiology, 2017)
The adoption of high-througput technologies demonstrated that in mature spermatozoa are present proteins that are thought to be not present or active in sperm cells, such as those involved in control of cell cycle. Here, by using an in silico approach based on the application of networks theory, we found that Cyclins/Cdk complexes could play a central role in signal transduction active during capacitation. Then, we tested this hypothesis in the vitro model. With this approach, spermatozoa were incubated under capacitating conditions in control conditions (CTRL) or in the presence of Aminopurvalanol A a potent, selective and cell permeable inhibitor of Cyclins/Cdk complexes at different concentrations (2μM, 10μM and 20μM). We found that this treatment caused the dose-dependent inhibition of sperm fertilizing ability. We attribute this event to the loss of acrosomes integrity due to the inhibition of physiological capacitation-dependent actin polymerization, rather than to a detrimental effect on membrane lipid remodelling or on other signalling pathways such as tubulin reorganization or MAPKs activation. In our opinion, these data could revamp the knowledge on biochemistry of capacitation and could suggest new perspectives in studying male infertility.